Prevalence and associations of keratoconus among children, adults, and elderly in the population-based Ural eye studies - Bikbov, Mukharram; Kazakbaeva, Gyulli M.; Gilmanshin, Timur R.; Iakupova, Ellina M.; Fakhretdinova, Albina A.; Tuliakova, Azaliia M.; Panda-Jonas, Songhomitra; Rusakova, Iuliia A.; Gilemzianova, Leisan I.; Khakimov, Dinar A.; Miniazeva, Liana A.; Usubov, Emin L.; et al. (Asia-Pacific journal of ophthalmology, 2023)
Purpose: - To estimate prevalence and associations of keratoconus in populations in Russia with an age from childhood to seniority. - Methods: - The study population consisted of the cohorts of 3 population-based studies performed in urban and rural areas within the same geographical region in Bashkortostan/Russia: the Ural Children Eye Study (UCES; age = 6-18 y; n = 4890), the Ural Eye and Medical Study (UEMS; age = >40 y; n = 5314), and the Ural Very Old Study (UVOS; age = >85 y; n = 651). Based on Scheimflug imaging, keratoconus was defined by a keratometric reading of ≥48 diopters (D) in any eye. - Results: - The mean maximal and minimal corneal refractive power increased from the UCES (43.58 ± 1.50 D and 42.70 ± 1.42 D, respectively) to the UEMS (44.26 ± 1.70 D and 43.61 ± 1.76 D, respectively) and to the UVOS (45.1 ± 1.72 D and 43.98 ± 1.68 D, respectively). Correspondingly, keratoconus prevalence increased from the UCES (42/4890; 0.086%; 95% CI = 0.060, 0.112) to the UEMS (112/5314; 2.11%; 95% CI = 1.72, 2.49) and to the UVOS (42/651; 6.45%; 95% CI = 4.56, 8.34). In the UCES, higher keratoconus prevalence was associated (multivariable analysis) with higher birth order [odds ratio (OR) = 2.34; 95% CI = 1.32, 4.15; P = 0.004], lower birth weight (OR = 0.99; 95% CI = 0.99, 0.99; P < 0.001), and shorter axial length (OR = 0.15; 95% CI = 0.08, 0.30; P < 0.001). In the UEMS, keratoconus prevalence correlated with shorter axial length (OR = 0.15; 95% CI = 0.10, 0.23; P < 0.001), larger corneal volume (OR = 1.17; 95% CI = 1.09, 1.25; P = 0.001), thicker lens (OR = 2.27; 95% CI = 1.06, 5.28; P = 0.04), cortical cataract degree (OR = 1.02; 95% CI = 1.01, 1.04; P = 0.01), and higher stage of age-related macular degeneration (OR = 1.65; 95% CI = 1.09, 2.51; P = 0.02). In the UVOS, keratoconus prevalence correlated with lower educational level (OR = 0.84; 95% CI = 0.71, 0.99; P = 0.04) and lower dynamometric handgrip force (OR = 0.92; 95% CI = 0.88, 0.97; P = 0.003). - Conclusions: - In this study on multiethnic groups from Russia, keratoconus prevalence increased from the pediatric group (0.09%) to the adult group (2.11%) and seniority group (6.45%), correlated mostly with biometric ocular parameters and was in all age groups statistically independent of most systemic parameters.
Elektronische Reproduktion der Druckausgabe
Gesehen am 04.04.2024